PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BALAI PENDIDIKAN DAN PELATIHAN KEHUTANAN PEKANBARU - Yessi Seftiani; Gimin '; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this research aims to determine the effect of work motivation and work environment to employee performance at the Forestry Education and Training Center Pekanbaru partially and simultaneously, with a sample size of 70 people. The sampling technique using purposive sampling method, that taking sample by using specific criteria. Data analysis methods use of multiple linear regression. Based on the results obtained F-value (28.092)> F-table (2; 57) = 3.159 means simultaneously motivation and work environment have a positive and significant impact on the performance of employees in Forestry Education and Training Center Pekanbaru. The results of the partial test for motivation variable t-value (7.140)> t-table (1.672) means work motivation influence on employee performance. Work environment variables with the t-value (2.491)> t- table (1.672) means that the working environment have a significant effect on the performance of employees in Forestry Education and Training Center Pekanbaru. The coefficient of determination obtained amounted to 0.490 it showed that 49.0% change in the performance of employees in Forestry Education and Training Center Pekanbaru determined by the independent variable which is the motivational factors and work environment, while 51.0% is determined by other factors.Keyword: Motivational, Work Environtment, Performance